Concentration of Total petroleum Hydrocarbons and Selected Heavy Metals In Soil And plant nearby Al-Nassiriya oil Refinery South of Iraq - k.k., Noora; y. AL-khafaji, Bassim (University of Thi-Qar Journal of Science, 2019)
The present study deal with measure concentration of Total petroleum hydrocarbons (TPHs) and selected heavy metals (HMs) (Cd , Pb , Co , V, and Ni) in soil and plant phragmits austriles (cav.) nearby AL-Nassiriya oil refinery during the period extended from winter up to summer 2018 . Some environmental factors such as , pH, salinity‰ , Electrical conductivity (Ec.) and soil temperature were measured , also total organic carbon (Toc) % content in soil was determined, and soil texture was analyzed and both of them expressed as percentage . The result observed that the range of the following factors were : soil temp. ranged from (26-36) ◦c , pH (7.3-7.9) , Ec. (14.3-25.3) µs/cm and salinity (5.1-7.3)‰ , while the value of Toc ranged from (0.7-8.55)% , soil texture was silty soil in control station , but they were sandy soil at polluted stations . The mean concentration of TPHs in soil , St.1 , St.2 , St.3 and St.4 were (16.47 ,14.78 ,12.65 and 1.36) µg /gm dry weight respectively , while the mean concentration of HMs in the soil for both season were Cd (0.78 ), Pb (26.85), Co (26.83), Ni (227.17) and V (95.67) µg /gm dry weight . In plant (shoot and root) part , mean concentration of TPHs were (4.86 and 8 .44) µg /gm dry weight respectively ,whereas the mean concentration of heavy metals in both parts for both seasons were Cd (0.49 and 0.65) , Pb (30.36 and 49.25) , Co (3.08 and 5.36 , Ni (8.01and 20 .38) and V (1.10 and 1.94) µg /gm dry weight respectively . It concluded from the present study that the oil refinery waste discharge affected upon the soil and plant of the study area through the increase in concentration of TPHs and HMs in its, also significant correlation observed between both pollutants and Toc content.